311. Preliminary results of the production of Ga-68 with biomedical cyclotron by liquid target. (December 2018) - Riga, S.; Cicoria, G.; Zagni, F.; Vichi, S.; Pancaldi, D.; Mora, L.; Marengo, M.
Abstract : Purpose: The aim of this work was to evaluate the feasibility of production of 68 Ga via the 68 Zn(p, n) 68 Ga reaction by proton irradiation of enriched zinc nitrate solution using a biomedical cyclotron, an alternative method to the current production through the 68 Ge/ 68 Ga generators. Methods: The target material was prepared by dissolving metallic 68 Zn (enrichment of 99.26%) in HNO3 6 N and then diluting it with HNO3 0.2 N to obtain a 1.7 M solution of 68 Zn(NO3 )2 [1] . Using the cross-section data (EXFOR database) and the proton stopping power (SRIM software), the 68 Ga saturation yield and its impurities were estimated. Irradiation tests were performed using the GE PETtrace cyclotron, located at our Institution. A liquid target was used, with a 25 μm foil of Havar® and a 250 μ m foil of Niobium, employed to obtain proper selection of entrance beam energy, to degrade the energy of the beam to 12 MeV in order to minimize the production of 67 Ga through the 68 Zn(p, 2n) 67 Ga reaction. The modification of the target also allowed us to improve resistance of the foil to acidity of the target material. Irradiations were carried out for 32 ± 1 min at 47 ± 2 μA. The product's activity was measured using an activity meter calibrated with a standard of 68 Ge traceable to NIST, while radionuclidic purity was evaluated by using gamma-ray spectrometry with an HPGe detector. Results: The gamma-spectra of the irradiated samples showed the presence of different isotopes of Ga, Cu and Co, as predicted by the theoretical estimates. Radionuclidic purity is within the limits of EU Pharmacopeia up to 3 h after end of bombardment. Separation and recovery up to a yield of 90 ± 9% was obtained. Conclusions: In summary, although optimizations and further advances are necessary, the results obtained are very promising and demonstrate the feasibility to produce sufficient activity of 68 Ga in cyclotron as a competitive alternative to the 68 Ge/ 68 Ga generators.